2020
DOI: 10.1109/lca.2020.3020064
|View full text |Cite
|
Sign up to set email alerts
|

Dagger: Towards Efficient RPCs in Cloud Microservices With Near-Memory Reconfigurable NICs

Abstract: The ongoing shift of cloud services from monolithic designs to microservices creates high demand for efficient and high performance datacenter networking stacks, optimized for fine-grained workloads. Commodity networking systems based on software stacks and peripheral NICs introduce high overheads when it comes to delivering small messages.We present Dagger, a hardware acceleration fabric for cloud RPCs based on FPGAs, where the accelerator is closely-coupled with the host processor over a configurable memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…2 showed that congested networks can have a dramatic impact on performance and power efficiency; similar observations have been made for cloud-based services [34,42,45,64,65,79,80,97,118]. The remote memory access framework above reduces the overhead of function communication, however, accelerating traditional RPCbased networking is still required, since the edge devices use RPCs to transfer data to/from the cloud [50,89,92,100,105,118]. For network acceleration, we piggyback on the same hardware platform used above.…”
Section: Hardware-based Networking Accelerationmentioning
confidence: 80%
See 1 more Smart Citation
“…2 showed that congested networks can have a dramatic impact on performance and power efficiency; similar observations have been made for cloud-based services [34,42,45,64,65,79,80,97,118]. The remote memory access framework above reduces the overhead of function communication, however, accelerating traditional RPCbased networking is still required, since the edge devices use RPCs to transfer data to/from the cloud [50,89,92,100,105,118]. For network acceleration, we piggyback on the same hardware platform used above.…”
Section: Hardware-based Networking Accelerationmentioning
confidence: 80%
“…The FPGA-based implementation significantly improves performance by bypassing the host's network stack, and the tight integration between the host and FPGA avoids the overheads of the PCIe interfaces [41,65,79,83,89,99,100]. HiveMind directly leverages the processor's cache coherence protocol to handle dirty data tracking and demand paging with no software involvement, thus reducing the remote memory access overhead.…”
Section: Fast Remote Memory Accessmentioning
confidence: 99%
“…2 showed that congested networks can have a dramatic impact on performance and power efficiency; similar observations have been made for cloud-based services [33,41,44,70,71,85,86,103,124]. The remote memory access framework above reduces the overhead of function communication, however, accelerating traditional RPC-based networking is still required, since the edge devices use RPCs to transfer data to/from the cloud [49,95,98,106,111,124]. For network acceleration, we piggyback on the same hardware platform used above.…”
Section: Hardware-based Networking Accelerationmentioning
confidence: 80%
“…The FPGA-based implementation significantly improves performance by bypassing the host's network stack, and the tight integration between the host and FPGA avoids the overheads of the PCIe interfaces [40,71,85,89,95,105,106]. HiveMind directly leverages the processor's cache coherence protocol to handle dirty data tracking and demand paging with no software involvement, thus reducing the remote memory access overhead.…”
Section: Fast Remote Memory Accessmentioning
confidence: 99%
“…These microservice components are composed via standardized Remote Procedure Calls (RPC) interfaces, such as Google's gRPC 3 or Facebook/Apach's Thrift 4 . The dependencies among components and their communication cost, once insignificant for monolithic applications, can now dominate the microservice regime 5,6 …”
Section: Introductionmentioning
confidence: 99%